Neo-Mandaic in Early Mandaean Colophons. Part 1: Linguistic Features - Morgenstern, Matthew (Aramaic studies, 2018)
Neo-Mandaic [NM] is a direct descendant of a dialect very close to its classical predecessor. By the time the earliest surviving Mandaean manuscripts were copied, spoken Mandaic already showed many of the developments that distinguish the modern vernaculars from the classical language. This article, the first of two, identifies those features. The second article presents the texts and a brief assessment of the sources of change.